2016
DOI: 10.1179/2047773215y.0000000035
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone/alum mixture a potent adjuvant for HIV-1 vaccine: induction of cellular and poly-isotypic humoral immune responses

Abstract: In the present study we used a fusion peptide from HIV-1 p24 and Nef as vaccine model and adjuvant activity of Naloxone/alum mixture was evaluated in a peptide vaccine model. HIV-1 p24-Nef fusion peptide was synthesized. Female BALB/c mice were divided into five groups. The first group immunized subcutaneously with the p24-Nef fusion peptide adjuvanted with Naloxone/alum mixture and boosted with same protocol. The second was immunized with fusion peptide adjuvanted in alum. The control groups were injected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Assessment of the IFN-c cytokine showed that mice immunized with the NLX/alumadjuvanted vaccine showed a significant increase in the IFN-c cytokine as compared with those immunized with alum-adjuvanted vaccine. The synergistic effect of NLX and alum in the induction of IFN-c and subsequent Th1 responses were consistent with the previous studies [17,26].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Assessment of the IFN-c cytokine showed that mice immunized with the NLX/alumadjuvanted vaccine showed a significant increase in the IFN-c cytokine as compared with those immunized with alum-adjuvanted vaccine. The synergistic effect of NLX and alum in the induction of IFN-c and subsequent Th1 responses were consistent with the previous studies [17,26].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, mice immunized with the NLX/alumadjuvanted vaccine exhibited a significant increase in the proliferation responses of lymphocytes when compared with those immunized with the alumand NLX-adjuvanted vaccines. This result showed the synergistic immunostimulating effect of NLX/ alum mixture on the lymphoproliferative response in vaccinated mice, as confirmed by other studies [15,17,26].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results of the studies demonstrated that the TSA gene was the most protective vaccine with the later including a CD8 + response. 132 , 142 146 DNA vaccine studies were performed in clinical trial Phases I and II and animals that were tested included dogs and mice. However, these promising results should be carefully considered and further confirmed by subsequent studies.…”
Section: Introductionmentioning
confidence: 99%